Representations of the 1918 Pandemic in poetry - Scerri, Mariella; Grech, Victor (Research and Humanities in Medical Education, 2020)
The Spanish flu does not have a powerful hold on cultural memory. As an illness, it erases the collective suffering; as a virus, it offers a degenerate body. This essay will explore representations of the 1918 pandemic in poetry by using three poems: Voigt's Kyrie, Eliot’s The Wasteland and Williams's Spring and All. The impact of the flu on these three poems not only consists of its material effects, but also resides in its metaphoric potential. Influenza provides an entry into modernist discourses across disciplines - literature, science, sociology, medicine - that are concerned with reconceptualising bodies of all kinds. The poems discussed in this paper echo the narrative of survivors from both the war and the flu who felt stranded in a state of existence describable as a "living death", a state in which one was not dead, but not quite alive, either. Surrounded by so many who were dying, the living often felt only half alive. The pervasive feeling of being on the threshold of life and death, and of confrontation between life and death, captures this particular historical moment on both literal and metaphorical levels. These poems also serve as contributors to modernist conceptions of the drudgery of everyday life during a pandemic and represent a factual description of what it was like to remain alive in 1919. They capture in their very silences both acknowledged horrors and horrors that remain unspoken.